ANALYSIS OF WORK MOTIVATION IN IMPROVING EMPLOYEE PERFORMANCE AT THE PRIVATE MADRASAH IBTIDAIYAH AL-MUBARAKAH MOHIYOLO (Jurnal Ilmu Manajemen dan Bisnis, 2025)
This study aims to analyze Work Motivation in Improving Employee Performance at Madrasah Ibtidaiyah Swasta Al-Mubarakah Mohiyolo. The method in this study uses descriptive qualitative methods with data collection techniques with observation, interviews and documentation. The results showed that work motivation plays an important role for employees to support their performance. Achievement, motivation, work relationships, self-development, and power and leadership are interconnected in creating a productive work environment. Success is not only seen from the results, but also from the learning process and its impact on others. Good relationships among coworkers and a supportive environment increase motivation, comfort and productivity. In addition, self-development through collaboration and a commitment to continuous learning are important in supporting competence. Wise leadership, supported by trust within the team, encourages responsibility, collaboration and work effectiveness.